2011
DOI: 10.1177/15648265110322s207
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Epidemiologic, Operational, and Sociopolitical Domains for Mainstreaming Nutrition

Abstract: Although undernutrition impacts a range of short-and long-term

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Capacity development for strategic and operational purposes needs to create and strengthen organizations and systems to support empowered workforces to achieve stated objectives. The type of organizational and systemic capacities required will depend on the choice of intervention(s) and delivery platform(s) ( 99 , 100 ). For example, in community-based programs such as the example from Nepal, the female community health workers needed to have the appropriate skills, supplies of IFA, and the time and motivation to deliver the intervention with quality to ensure uptake, despite barriers experienced by users.…”
Section: Resultsmentioning
confidence: 99%
“…Capacity development for strategic and operational purposes needs to create and strengthen organizations and systems to support empowered workforces to achieve stated objectives. The type of organizational and systemic capacities required will depend on the choice of intervention(s) and delivery platform(s) ( 99 , 100 ). For example, in community-based programs such as the example from Nepal, the female community health workers needed to have the appropriate skills, supplies of IFA, and the time and motivation to deliver the intervention with quality to ensure uptake, despite barriers experienced by users.…”
Section: Resultsmentioning
confidence: 99%
“…A sixth example (funded by the World Bank for the explicit purpose of creating actionable knowledge) is the Mainstreaming Nutrition Initiative, which conducted engaged, prospective research in 5 countries for the explicit purpose of developing "process guidance" on how to elevate and sustain nutrition on national policy agendas. That research was guided by broad, transdisciplinary conceptual frameworks of the policy process (103,135), the findings of earlier work on global health (136,137), and the principles of grounded theory (138). These methodological strategies identified broadly relevant dynamics and strategies in the policy process that received inadequate attention in earlier work (93,(139)(140)(141)(142)(143).…”
Section: Nutrition Policymentioning
confidence: 99%
“…In addition to financial resources, this framework asserts that feasibility depends on the degree of the intervention's technical complexity in four domains: (a) intervention characteristics, (b) delivery characteristics, (c) government capacity requirements, and (d) usage characteristics (for detailed information, see Table 1). This framework has previously been used to assess complexity of a range of health interventions including condom promotion (Gericke et al, 2005), tuberculosis directly observed treatment, short-course (DOTS) programs (Gericke et al, 2005), diet improvement (Snowdon et al, 2010), and food poisoning risk reduction strategies (Wu & Khlangwiset, 2010), as well as identifying strategies to improve nutrition mainstreaming (Menon et al, 2011).…”
mentioning
confidence: 99%